Visit of Yugoslav president Josip Broz to Egypt (28. 12. 1955 - 06. 01. 1956) - Živković Milutin D. (Baština, 2018)
The trip of the Yugoslav delegation to Egypt took place at the end of December 1955. It was a demanding diplomatic campaign. In the course of ten-day stay in the country situated on the Nile River, Josip Broz Tito had several conversations with Gamal Nasser. He used the occasion to present Gamal Nasser with the foreign affairs platform of peaceful coexistence that was created by Yugoslavia. In compliance with the wishes of the West, his intention also was to propose to Nasser a peaceful solution of the problems with Israel. Egyptian president, however, rejected this proposal. Therefore, Yugoslav diplomacy supported Egypt and by confronting the interests of the West which threatened this African country, routed its own path at the international scene divided into blocks.